2020
DOI: 10.1136/archdischild-2019-317663
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and childhood illnesses in Cambodia: a cross-sectional study

Abstract: BackgroundAround a quarter of Cambodian women reported being victim to intimate partner violence (IPV) from their current partner. Children’s exposure to familial IPV impacts psychosocial well-being and emerging research indicates associations with physical health.ObjectiveInvestigate associations between maternal experience of IPV and common childhood illnesses in Cambodia.Design, setting, participantsAnalysis of the Cambodia Demographic and Health Survey (2000, 2005, 2014) using logistic regression, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(42 reference statements)
1
7
0
2
Order By: Relevance
“…The results of this cohort show the distribution of FGIDs in a sample of children from a low-income community, exposed or not to IPV committed against their mother. The occurrence of CEIPV increased the chance of FGIDs, as identified in other international studies, 17 , 18 , 19 even after controlling for confounding variables.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The results of this cohort show the distribution of FGIDs in a sample of children from a low-income community, exposed or not to IPV committed against their mother. The occurrence of CEIPV increased the chance of FGIDs, as identified in other international studies, 17 , 18 , 19 even after controlling for confounding variables.…”
Section: Discussionsupporting
confidence: 62%
“…The greater chance of FGIDs when CEIPV started in the first two years of life, identified in the present study, corroborates the international literature that also shows harmful effects on the physical health of children exposed to violence early in life, despite verifying different ages from the one the authors analyzed. 17 , 18 , 19 This occurrence can be explained due to the brain structures responsible for managing the stress response and emotional control are slow to develop early in life; therefore, the earlier the exposure, the more susceptible the child becomes to the damage caused by ACEs. 23 Exposure to adversities in childhood increases the risk of health problems throughout life, 17 , 18 due to the greater plasticity and vulnerability of the child's brain to environmental effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, emotional violence was associated with an increased likelihood of diarrhoea, fever, and acute respiratory tract infection. Nakphong and von Ehrenstein (2020) discovered, in their study in Cambodia, that the mothers' experiences of emotional IPV was associated with diarrhoea, acute respiratory tract infection, and fever in the children. In our study, no relationship was found between mothers' IPV experiences and children's emergency diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these children may experience psychological problems, such as dysfunctional behaviors, anxiety, and hostility and may attempt suicide (Blair et al, 2015;Durand et al, 2011;Maddoux et al, 2015 ). In addition, this psychological and social stress can cause physical problems, including an increased risk of asthma (Bair-Merritt et al, 2015), diarrhea, and acute respiratory infections (Nakphong & von Ehrenstein, 2020).…”
Section: Introductionmentioning
confidence: 99%